Elevating Insulin Signaling Using a Constitutively Active Insulin Receptor Increases Glucose Metabolism and Expression of GLUT3 in Hippocampal Neurons - Frazier, Hilaree N.; Ghoweri, Adam O.; Anderson, Katie L.; Lin, Ruei-Lung; Popa, Gabriel J.; Mendenhall, Michael D.; Reagan, Lawrence P.; Craven, Rolf J.; Thibault, Olivier (Frontiers in Neuroscience, 2020)
Insulin signaling is an integral component of healthy brain function, with evidence of positive insulin-mediated alterations in synaptic integrity, cerebral blood flow, inflammation, and memory. However, the specific pathways targeted by this peptide remain unclear. Previously, our lab used a molecular approach to characterize the impact of insulin signaling on voltage-gated calcium channels and has also shown that acute insulin administration reduces calcium-induced calcium release in hippocampal neurons. Here, we explore the relationship between insulin receptor signaling and glucose metabolism using similar methods. Mixed, primary hippocampal cultures were infected with either a control lentivirus or one containing a constitutively active human insulin receptor (IRβ). 2-NBDG imaging was used to obtain indirect measures of glucose uptake and utilization. Other outcome measures include Western immunoblots of GLUT3 and GLUT4 on total membrane and cytosolic subcellular fractions. Glucose imaging data indicate that neurons expressing IRβ show significant elevations in uptake and rates of utilization compared to controls. As expected, astrocytes did not respond to the IRβ treatment. Quantification of Western immunoblots show that IRβ is associated with significant elevations in GLUT3 expression, particularly in the total membrane subcellular fraction, but did not alter GLUT4 expression in either fraction. Our work suggests that insulin plays a significant role in mediating neuronal glucose metabolism, potentially through an upregulation in the expression of GLUT3. This provides further evidence for a potential therapeutic mechanism underlying the beneficial impact of intranasal insulin in the clinic.